Pemenuhan hak Pendidikan anak penyandang disabilitas di SLB Autisma YPPA Bukittinggi - Fidella Khairunnisa; Irwan Hamdi; Maria Montessori; Fatmariza Fatmariza (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This research is motivated by the importance of fulfilling the right to education for children with disabilities as part of the basic rights of citizens, which in practice still faces various limitations in educational services that are appropriate to the needs of students. This study aims to describe and analyze the form of fulfillment of the right to education for children with disabilities at the Special Needs School for Autism of the Child Potential Development Foundation (YPPA) in Bukittinggi City. The research uses a qualitative approach with a case study type. Data were collected through interviews with the principal, teachers, and parents, observations of learning and school activities, and documentation of school programs and student data. The results show that the fulfillment of the right to education is carried out through learning that is adapted to the conditions and needs of each child, covering aspects of knowledge, attitudes, and skills. The school implements individual learning, intensive mentoring, behavioral habits, and skills and independence activities to support student development. This study concludes that the Special Needs School for Autism of YPPA has played a role in fulfilling the right to education for children with disabilities in an adaptive and sustainable manner, although strengthening supporting facilities and program development are still needed to improve the quality of educational services.